Efficacy and safety of airway stent placement in the treatment of airway esophageal fistula - Li, Xiangnan; Luo, Peiyuan; Zhao, Mengyu; Wen, Feifei; Jiang, Guancheng; You, Yibei; Liu, Yaru; Wu, Xuan; Herth, Felix; Zhang, Quncheng (Respiration, 2025)
Introduction: This study aimed to evaluate both the clinical efficacy and safety of airway stent placement in the treatment of patients with esophageal cancer-associated airway esophageal fistula (AEF). The focus is on evaluating improvements in patient survival and quality of life. Methods: Overall, this study enrolled 111 patients diagnosed with esophageal cancer-associated AEF. Among them, 50 (45.0%) and 61 (55.0%) patients received airway stent placement and conservative treatment, respectively. Follow-up assessments were conducted to determine the clinical efficacy and safety of the interventions, with survival and quality of life as the primary endpoints. Results: By the end of the follow-up, 98 of 111 patients (88.3%) had died, leaving 13 survivors (11.7%). Patients with esophageal cancer-associated AEF had an overall mean survival time of 147.4 (95% CI, 123.9-170.9) days. Patients in the stent placement group had a mean survival of 192.5 (95% CI, 151.2-233.7) days, which was significantly longer than the 110.0 (95% CI, 88.1-131.8) days in the conservative treatment group (p < 0.001). Sex (p = 0.017), tumor stage (p = 0.030), surgery (p = 0.005), pulmonary infection (p < 0.001), fistula size (p < 0.001), and pre-Karnofsky Performance Status (KPS) (p < 0.001) were the independent risk factors affecting survival. Furthermore, patients in the stent placement group demonstrated improved KPS scores post-treatment, increasing from 48.2 to 57.9 (p = 0.017). Conclusion: Airway stent placement is beneficial in alleviating the symptoms, quality of life, and survival of patients with esophageal cancer-associated AEF.
Veröffentlicht: 17. Februar 2025
Gesehen am 29.09.2025